Geoeconomic Uses of Global Warming: The “Green” Technological Revolution and the Role of the Semi-Periphery - Hurtado de Mendoza, Diego Fabian (2018)
While some semi-peripheral countries have seen renewable energies as an opportunity to build their industrial and technological capacities, core countries and global governance organizations have been promoting “green growth.” Since the 2008 global financial crisis, global warming has been used as a catalyst for big business. As the global economy may be entering the first stage of a “green industrial revolution,” neo-Schumpeterian economists have regained visibility. We intend to show how, as a consequence of the lack of a world-systemic perspective, crucial inconsistencies arise in neo-Schumpeterian contributions that weaken their conceptualization of the role of non-core economies in technological change. We examine the case of the tortuous trajectory of wind energy in Argentina to show the specific organizational, institutional, and macroeconomic constraints faced by a semiperipheral economy as it attempts to develop its own technological and industrial capacities. The neoSchumpeterian view of the “green industrial revolution” must be understood as valid only for the core-economy subsystem, which seems to require as well polarization of the world-system through what we call “semi-peripheral neoliberalism,” a peripheralizing force upon the semi-periphery necessary in order to rejuvenate core economies.